Management of Spina Bifida Related Non Idiopathic Club-Foot with Ponseti’s Method - Shafiq Ahmad, Shakeel Ahmed, Mahreen Zahra, Amir Hanif, Bilal Hussain, Muhammad Kashif (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the outcome of Ponseti’s method among children with spina bifida related non-idiopathic clubfoot at a leading pediatric tertiary care children hospital of South Punjab, Pakistan. Study Design: A retrospective cohort. Place and Duration of the Study:Department of Pediatric Orthopedic Surgery, The Children’s Hospital and Institute of Child Health, Multan Pakistan from 1st January 2016 to 31st March 2022. Material and Methods: A total of 24 children (41 feet)of both genders aged up to 3 months presenting with non-idiopathic clubfoot related to spina bifida who underwent Ponseti’s method for treatment of clubfoot, with a minimum post-treatment follow up of 3 years were included. Demographic data, severity of clubfoot disease along outcomes in terms of successful correction, unsuccessful correction, relapse were noted during the study period. Results: In a total of 24 children, 15 (62.5%) were boys. Overall, mean age was calculated to be 2.6±2.2 weeks while 14 (58.3%) children were aged between 0-2 weeks. Bilateral feet were involved in 17 (70.8%) children while unilateral feet involvement was noted in 7 (29.2%) cases so total number of feet were 41. Out of these 41 feet, 38 (92.7%) had severity of clubfoot as per Pirani Score as 6. Number of casts performed were 8 or below in 39 (95.1%). Mean duration of follow up was 3.8±0.6 years. Correction of clubfoot was achieved in 36/41 (87.8%) feet. During the follow-ups, recurrence occurred in 11 (26.8%) feet. Conclusion:Initial clubfeet correction in the spina bifida cases achieved good correction rates. Rate of recurrence was considerably high with a minimum follow up period of 3 years among spina bifida associated clubfeet.